Intensive investigation on hydrogen storage properties and reaction mechanism of the NaBH4-Li3AlH6 destabilized system. (13th August 2019) - Yahya, M.S.; Ali, N.A.; Sazelee, N.A.; Mustafa, N.S.; Halim Yap, F.A.; Ismail, M.
Abstract: Notable effects of Li3 AlH6 on the hydrogen storage properties of the NaBH4 are studied intensively. Li3 AlH6 is synthesized by milling 2LiH-LiAlH4 mixture for 12 h. The best molar ratio of the NaBH4 - Li3 AlH6 destabilized system is 1:1 which has decomposed at two stages; Li3 AlH6 decomposition stage at 170 °C and NaBH4 decomposition stage at 400 °C. As no significant effect on the decomposition temperature between 1 h and 24 h of milling time can be observed, the 1-hour milling preparation method is selected for the characterization. Isothermal absorption has shown that the system is able to absorb 4.2 wt% and 6.1 wt% of hydrogen in 60 min at 330 °C and 420 °C under 30 atm of hydrogen pressure. In contrast, only about 3.4 wt% and 3.7 wt% of hydrogen can be absorbed by the milled NaBH4 under a similar condition. Meanwhile, the system is able to desorb 2.0 wt% and 4.1 wt% of hydrogen in 60 min at 330 °C and 420 °C in isothermal desorption while only 0.3 wt% and 2.1 wt% can be released by the milled NaBH4 under the similar condition. The decomposition activation energy and enthalpy of the NaBH4 stage are calculated to be 162.1 kJ/mol and 68.1 kJ/mol H2 . Based on the X-ray diffraction analysis, Na, Al and AlB2 are formed during the dehydrogenation process. The formation of Al and AlB2 are the keys to the improvement of hydrogenation properties. It is concluded that Li3 AlH6 is a good destabilizing agent for the NaBH4 system. Highlights: The H2 storage properties of NaBH4 -Li3 AlH6 have been studied for the first time. The best molar ratio of the NaBH4 -Li3 AlH6 destabilized system is 1:1. The system is able to absorb 6.1 wt% of H2 in 60 min. The Ea and enthalpy of the NaBH4 are calculated to be 162.1 kJ/mol and 68.1 kJ/mol H2 .